2017
DOI: 10.18203/2394-6040.ijcmph20172060
|View full text |Cite
|
Sign up to set email alerts
|

Factors for non-acceptance of contraceptive methods amongst married women of reproductive age group in rural Patna

Abstract: INTRODUCTIONIndia is the second most populous country in the world with a population of more than 1.2 billion population explosion has been India's major problem since independence.1 It is a major obstacle to the overall progress of the nation. The explosive growth of human population combined with unsustainable production and consumption pattern, is putting increasing stress on air, water, land, energy and other essential resources.There are a number of factors that affect population growth in India. These in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
2
10
0
Order By: Relevance
“…Other reasons for the high unmet need, in our study, were young age of the last child and time constraints with no one to look after the family, especially children, during and after hospitalization for operation. Similar reasons for the unmet need are observed by Haldar et al ,[ 20 ] Shree et al ,[ 23 ] Sudha et al ,[ 9 ] Valekar et al ,[ 24 ] Durowade et al ,[ 25 ] and the RESPOND project in Nigeria[ 26 ] in their studies, but they have considered the total unmet need instead of unmet need for permanent methods only. Also, the studies have been conducted in different regions and cultural settings that can explain the different frequencies of the reasons specified.…”
Section: Discussionsupporting
confidence: 60%
“…Other reasons for the high unmet need, in our study, were young age of the last child and time constraints with no one to look after the family, especially children, during and after hospitalization for operation. Similar reasons for the unmet need are observed by Haldar et al ,[ 20 ] Shree et al ,[ 23 ] Sudha et al ,[ 9 ] Valekar et al ,[ 24 ] Durowade et al ,[ 25 ] and the RESPOND project in Nigeria[ 26 ] in their studies, but they have considered the total unmet need instead of unmet need for permanent methods only. Also, the studies have been conducted in different regions and cultural settings that can explain the different frequencies of the reasons specified.…”
Section: Discussionsupporting
confidence: 60%
“…Also amongst socio-demographic factors, marriage was also associated with non-use of contraceptive. This finding was previously linked to the desire to have children within marriage, cultural norms or opposition by the husbands [23,24,7]. This finding could also suggest that the majority of unmarried AGYW are using contraceptives.…”
Section: Discussionmentioning
confidence: 72%
“…8,9 Contrary to these results, Vijay Sree and colleagues reported different age group characteristics as majority of the study subject were within age group 20-30 years and were illiterate. 10 The findings of the present research study indicated that all the women had ever heard of family planning methods and their main source of information were friends/families and health workers respectively. Consistent results have been seen in the study conducted by Uma where almost 82% women were aware about family planning methods and most of them received information about FP methods from Health personnel.…”
Section: Discussionmentioning
confidence: 59%